AN ANALYSIS OF CULTURAL WORD TRANSLATION AS OBSERVED IN ARTHUR GOLDEN'S NOVEL ENTITLED MEMOIRS OF A GEISHA - Hety Hardianty, - (2008)
The research entitled AN ANALYSIS OF CULTURAL WORD TRANSLATION AS OBSERVED IN ARTHUR GOLDEN'S NOVEL ENTITLED MEMOIRS OF A GEISHA is an analysis of cultural word contained in the novel and its procedure of translation used. Often there are some obstacles in translating the specific word that refers to the things, events, or customs, which are peculiar to some short of countries. It is caused by the different culture that exists among the countries. Moreover, sometimes the translator does not find the equivalent word from the Source Language into the Target Language. That is to say, a translator not only has to master the language, but also the culture of the related countries. The novel involves quite much of Japanese culture. Indeed, it is a big challenge and also needs hard work for the researcher to deal with some of Japanese words and cultures, which are unfamiliar. The study applied a descriptive qualitative method by using random sampling and purposive sampling. The result showed that cultural word highest rank positioned by material category, followed by social category, the rest are organization, ecology, and gesture. While the most frequent procedure used in translating cultural word is transference followed by transpositions, cultural equivalent, naturalisation, literal translation, couplet, synonymy, paraphrase, and descriptive equivalent. The finding of this study is expected to give a wider horizon about the culture in the world, especially Japan, and also can add and enrich the knowledge of cultural word. Furthermore, it will give some fruitful ideas for further study in this research